May AI Revolution Be Labour-Friendly? Some Micro Evidence from the Supply Side - Giacomo Damioli; Vincent Van Roy; Daniel Vertesy; Marco Vivarelli (Institute of Labor Economics (IZA), 2021)
This study investigates the possible job-creation impact of AI technologies, focusing on the supply side, namely the providers of the new knowledge base. The empirical analysis is based on a worldwide longitudinal dataset of 3,500 front-runner companies that patented the relevant technologies over the period 2000-2016. Obtained from GMM-SYS estimates, our results show a positive and significant impact of AI patent families on employment, supporting the labour-friendly nature of product innovation in the AI supply industries. However, this effect is small in magnitude and limited to service sectors and younger firms, which are the leading actors of the AI revolution. Finally, some evidence of increasing returns seems to emerge; indeed, the innovative companies which are more focused on AI technologies are those obtaining the larger impacts in terms of job creation.
Keywords: O33; 330; innovation; technological change; patents; employment; job-creation